MANAJEMEN PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DAN URGENSINYA DALAM MENGHADAPI ERA SOCIETY 5.0 - Dwi Wulan Sari; M. Isa Anshori; Alviani Nur Baiti Rohmah; Widya Wulan Dari (Universitas Islam Lamongan, 2023)
The curriculum is always dynamic and undergoes periodic development. The curriculum evolves according to the underlying circumstances and demands. This study aims to examine the managerial pattern of constructing an Islamic education curriculum in response to the society 5.0 era. This study found, using qualitative methodologies, that in preparation for the period of society 5.0, the Islamic education curriculum emphasizes religious knowledge and technological abilities. The management of curriculum development, on the other hand, is also geared towards building the appropriate attitudes, knowledge, and abilities for comprehending the rapid advancement of technology. So that technological advances do not impede the internalization of religious knowledge and attitudes pertinent to the Society 5.0 age.